Hubungan Faktor Predisposisi dan Enabling Kepala Keluarga Dengan Perilaku Penggunaan Jamban Sehat di Dusun Aster Desa Piru Kabupaten Seram Bagian Barat Provinsi Maluku - Elvans Soumokil; Asrijun Juhanto; Rahmawati Azis (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Healthy latrines are an important sanitation facility that aims to maintain environmental health and improve public health in general. However, in Aster Hamlet ownership of healthy latrines is still low. Of the 345 families in Aster Hamlet, only 73 have healthy toilets, leaving 272 other families who do not. The habit of defecating into the river is a common practice there, considering that most of the houses are located near the river The aim was to identify factors related to the behavior of using healthy toilets in Aster Hamlet. This research used a cross-sectional design. The research population was 345 heads of families. The research sample was taken from 73 heads of families who had healthy latrines using total sampling technique. The analysis carried out included univariate, bivariate and multivariate analysis to gain a comprehensive understanding of the factors that influence healthy latrine use behavior. The results showed that all the variables studied, namely knowledge (p = 0.003), attitudes (p = 0.000), facilities and infrastructure (p = 0.002), and water availability (p = 0.000), had a significant relationship with latrine use behavior. Healthy. In particular, the most related variable is water availability, with the highest Exp(B) value of 2.505. This shows the importance of the water availability factor in influencing the behavior of using healthy latrines in Aster Hamlet, Village